Evaluating the impact of community interventions on childhood obesity in populations living in low‐income households in Los Angeles: A simulation study. Issue 11 (28th June 2022) - Nianogo, Roch A.; Mueller, Megan P.; Keeler, Bryce; Kreuger, Kurt; Nhan, Lilly A.; Nobari, Tabashir Z.; Crespi, Catherine M.; Osgood, Nathaniel; Kuo, Tony; Prelip, Michael; Wang, May C.
Summary: Background: The complex multifactorial nature of childhood obesity makes community interventions difficult to evaluate using traditional approaches; innovative methods are needed. Objective: To evaluate the impact of various interventions targeting childhood obesity‐related behaviours, and classified as using a micro‐level (e.g., home visitation programs) or macro‐level (e.g., business practices) strategy, on obesity among children enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Methods: We simulated a population of 1500 children enrolled in WIC, with specific diet, physical activity, breastfeeding behaviours and body mass index z‐scores (BMIz), following them from age 2 to 5 years. Results: Combined interventions targeting breastfeeding appeared to be moderately effective, reducing BMIz by 0.03 (95% CI −005, −0.01). Two strategy‐specific interventions, home visitation programs and business practices targeting obesity‐related behaviours, appeared to be moderately effective at reducing BMIz by 0.04 (95% CI −0.06, −0.02) and 0.02 (95% CI −0.04, 0.00), respectively. Contrary to expectation, combining all micro and macro interventions appeared to have no impact or moderately increased the proportion of obesity/overweight among children. Conclusion: Interventions targeting breastfeeding behaviour were most effective when both micro and macro strategies were implemented. Interventions targeting obesity‐related behaviours in general were effective for two strategies, home visitation and business practices.